A conceptual framework for the electronic performance support systems within IBM lotus notes 6 (LN6) example - (:unkn) unknown (My University, 2005)
The concept of Electronic Performance Support Systems (EPSS) is containing multimedia or computer based instruction components that improves human performance by providing process simplification, performance information and decision support system. EPSS has become a hot topic for organizational development, human resources, performance technology, training, and educational development professionals. A conceptual framework of EPSS is constructed under five interrelated and interdependent domains for educational implications. The domains of the framework are online collaboration, cost-effectiveness, motivation, service management, and performance empowering. IBM Lotus Notes 6 (LN6) is used as an example application tool to illustrate the power of this framework. The framework describes a set of relevant events based upon deductive analyses for improving our understanding of the EPSS and its implications on education and training. The article is also pointed out that there are some similarities between the EPSS' and the LNS's specific features within this conceptual framework. It can provide some guidelines and benefits to researchers, educators, and designers as well.
Keywords: Conceptual Framework; EPSS; Lotus Notes 6; Training and Education